Improving the care of people affected by post-COVID syndrome (LCovB):study protocol of a mixed-methods study - Jennifer Marie Burchardi; Martin Brünger; Helma Freitag; Anna Brock; Carmen Scheibenbogen; Natalie Kohzer; Ellen Kexel; Raphael Kohl; Lea Rückgauer; Eva Schmitz; Andrea Budnick; Johanna Schuster (PLoS ONE, 2026)
Background The COVID-19 pandemic has resulted in a large number of individuals affected by post-COVID syndrome (PCS) and poses significant challenges to healthcare provision. Many PCS patients are left to manage their condition without adequate support. The aim of the LCovB study is to collect data on symptoms (including pre-existing conditions and comorbidities) and the care situation and trajectories of PCS patients. The results will serve to identify key measures for optimizing care. Methods Using a mixed-methods approach, the study includes secondary data analyses of routine data of PCS patients from 44 German statutory health insurance companies, a primary survey and semi-structured interviews with selected PCS patients. In addition, the situation of severely ill patients will be assessed through a physician’s visit and questionnaires. Finally, an expert panel with stakeholders from the healthcare sector will examine the study results using the Delphi method to derive recommendations for treatment and optimized care pathways. Discussion The LCovB study examines care trajectories to identify gaps and barriers for patients with PCS, aiming to develop evidence-based recommendations and guidelines for care and disease management, supported by an expert panel. Trial registration In August 2025, the study was prospectively registered in the German Clinical Trials Register: Module 1 (DRKS00037341), Module 2 (DRKS00037343), Module 3 (DRKS00037344), Module 4 (DRKS00037345).